The effect of intellectual capital towards financial performance of companies: an analysis of manufacturing sector in Malaysia / Nur Safinas Abdul Rahman - Abdul Rahman, Nur Safinas (Faculty of Business Management, 2017)
Briefly, this research is related to financial performance. As the title, intellectual capital and financial performance, this study was conducted based on the observation and data collected from food industries’ firms. Many of previous studies are using banking, automobile and corporate sector as their preferences of the study. Intellectual capitals are also known as the background for some companies to perform well in business activities but not all firms take this step into action. Thus, some firms may have lead to low performance in the market. Previous studies also proved that big firms like corporate governance who take seriously about intellectual capital have better performance than firms who doesn’t. In simpler words, the firms make some investments for something that is called intangible assets which can make a big impact to the company itself. Regarding the variables used, the dependent variables selected comprises of two components to measure financial performance which are Return on Assets (ROA) and Return on Equity (ROE). For independent variable, the method used to measure Intellectual Capital is the Value Added Intellectual Capital (VAIC). This is a model developed by Pulic (1998). He also proposed the use of value added as an indicator measuring performance in a knowledge economy context. But, regarding this topic, how Intellectual Capital can contribute towards manufacturing sector which specialized into food sector. This will be further explained through this study. The sample taken is from 10 companies specialized in food making and processing. The sampling year is conducted from 2005 until 2014.